Metod Penentuan Kelas Interval Pada Peta Statistiki - Perpustakaan UGM, i-lib ([Yogyakarta] : Jur. Budidaya Pertanian Fak. Pertanian UGM, 1996)
Thematic Maps, such as statistic maps, that provide quantitative information are used more widely in the society. In other to produce statistic map that provide accurate and more understandable quantitative information, it is necessary to select the most suitable method to determine class intervals. It is expected that the use of the suitable will result in information that closely represents the real world. This research, four method : Equal method, standard deviation, Geometric progress, and arithmetic progress to compute interval class commonly used in cartography. The analysis was done by comparing graphics of class intervals and diagram scatter diagrams of each method. The research found that the geometric progress provided the best result